Petrology and metamorphism of sapphirine-bearing aluminous gneisses from Tonagh Island in the Napier Complex, East Antarctica - Hokada, Tomokazu; Osanai, Yasuhito; Toyoshima, Tsuyoshi; Owada, Masaaki; Tsunogae, Toshiaki; Crowe, Warwick A. (National Institute of Polar Research, 1999)
P(論文) A variety of Mg-rich silica-undersaturated aluminous gneisses containing sapphirine, spinel and corundum occur within the ultrahigh-temperature (UHT) metamorphic sequence at Tonagh Island in the Napier Complex, East Antarctica. They occur as blocks or pods in quartzo-feldspathic gneisses or mafic granulite, or as thin layers around ultramafic rocks. The modes of occurrence, constituent minerals and mineral textures of these aluminous gneisses are different from each other, suggesting that they are derived from different protoliths or formation processes. Field occurrences suggest that some of the aluminous gneisses on Tonagh Island may not be simple pelitic precursors but were formed through processes associated with partial melting or metasomatism. Various reaction textures and compositional zoning in constituent minerals, which reflect retrograde metamorphism, are commonly observed in these rocks. Garnet-orthopyroxene geothermobarometry using the chemical compositions of the cores of garnet and orthopyroxene yields slightly lower temperatures (800-1000℃ at 0.5-1.0 Gpa) than the thermal climax (1100℃). Pressure condition of 0.8-1.1 Gpa at the thermal peak (1030-1100℃) is estimated from the garnet-orthopyroxene geobarometry. departmental bulletin paper